Sutureless and glue-free conjunctival autografting versus sutured autografting for primary pterygium: a prospective comparative study - Sahu, Shivangi; Shrivastava, Shiva; Shah, Ankit (International Journal of Research in Medical Sciences, 2026)
Background: Pterygium recurrence remains a major challenge following surgical excision. Although conjunctival autografting is the preferred treatment, suturing is associated with postoperative discomfort and suture-related complications. This study compared the outcomes of sutureless and glue-free conjunctival autografting with sutured conjunctival autografting in primary pterygium. Methods: A prospective, observational, comparative hospital-based study was conducted at a tertiary-care centre in Madhya Pradesh, India, from February 2021 to February 2022. A total of 50 patients with primary nasal pterygium were included and divided into two groups: (i) sutureless and glue-free conjunctival autografting (n=25), and (ii) sutured conjunctival autografting (n=25). Patients were evaluated preoperatively and followed up at 2, 4, and 6 weeks postoperatively. Results: Most patients i.e. 15 (30.0%) were aged 31-40 years. Males comprised 23 (46.0%) patients of the study population. Majority i.e. 32 (64.0%) patients resided in rural areas. Progressive pterygium was observed in 46 (92.0%) patients, with grade 2 being the most common presentation as observed in 36 (72.0%) patients. At the 6-week follow-up, visual acuity of 6/9-6/6 was achieved in 20 (80.0%) patients in the sutureless group and 17 (68.0%) patients in the sutured group. Graft oedema was observed in 2 (8.0%) and 1 (4.0%) patients, while graft displacement occurred in 2 (8.0%) and 1 (4.0%) patients in the sutureless and sutured groups, respectively. Pain was less frequent in the sutureless group at follow-up. Recurrence was observed in 2 (8.0%) patients in the sutureless group and 1 (4.0%) patients in the sutured group. Conclusions: Sutureless and glue-free conjunctival autograft technique is easy, safe, effective.